2007
DOI: 10.1159/000098066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sexual Function in Women with Overactive Bladder Syndrome

Abstract: Introduction: Of late, little data is available concerning factors affecting female sexual function. In the present study, we evaluated the effects of overactive bladder (OAB) syndrome symptoms on female sexual function. Materials and Methods: 40 patients with OAB symptoms and 40 age-matched women as a control group were evaluated using the Female Sexual Function Index (FSFI) for sexual function. According to the presence of urge incontinence, women with OAB were also divided into wet and dry groups. After com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…Thus, we cannot support the findings by Ghielmetti et al [4] or David-Montefiore et al [23] that prolapse operations, particularly posterior re- pair, deteriorate sexual function, or that incontinence procedures negatively affect sexual function. Our findings correlate to the findings by Marszalek et al [16] and Sen et al [17]. A limitation of our study is the small number of sexually active patients in the concomitant operation subgroup.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, we cannot support the findings by Ghielmetti et al [4] or David-Montefiore et al [23] that prolapse operations, particularly posterior re- pair, deteriorate sexual function, or that incontinence procedures negatively affect sexual function. Our findings correlate to the findings by Marszalek et al [16] and Sen et al [17]. A limitation of our study is the small number of sexually active patients in the concomitant operation subgroup.…”
Section: Discussionsupporting
confidence: 91%
“…To date, little is known about the impact of prolapse and urinary incontinence surgery on the female sexual life [16,17], and no data about laparoscopic prolapse sur- Values denote means with SD in parentheses, or numbers with 95% CI in parentheses. OP = Operation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated a strong association between pelvic floor disorders, lower urinary tract symptoms, overactive bladder with or without urinary incontinence, and FSD [7–14]. The prevalence of FSD in sexual active women attending a urogynecologic outpatient clinic ranges from 48% to 64% [15,16], which is higher than the aforementioned 43% in the general population.…”
Section: Introductionmentioning
confidence: 98%
“…The prevalence of female sexual dysfunction (FSD) in menopausal women differs according to several factors; in the longest population study, which was held in Australia [7], the prevalence of FSD ranged from 42% to 88%.…”
Section: Introductionmentioning
confidence: 99%